Early and late mortality after myocardial infarction in men and women: prospective observational study. Issue 3 (14th February 2005) - Griffith, D; Hamilton, K; Norrie, J; Isles, C
Abstract : Objective: To compare characteristics, management, and outcome of myocardial infarction (MI) in men and women. Design: Prospective observational study. Setting: District general hospital in southwest Scotland. Participants: 966 men and 597 women admitted with first MI between 1994 and 2000 with follow up to the end of 2001. Results: 393 (40.7%) men and 305 (51.1%) women died during a median follow up of 3.4 years for the survivors. Univariate analysis indicated an excess mortality among women (hazard ratio (HR) 1.45, 95% confidence interval (CI) 1.25 to 1.68), which disappeared after adjustment for age, smoking, co-morbidity, previous vascular disease, diabetes, hypertension, and social deprivation (HR 1.02, 95% CI 0.87 to 1.20). There was also an excess early mortality within 30 days among women (HR 1.54, 95% CI 1.20 to 1.98), though this did not retain significance after adjustment for the same covariates (HR 1.04, 95% CI 0.79 to 1.37). Small and insignificant differences were found in the proportion of men and women receiving thrombolysis on admission and secondary prophylactic drugs at discharge, except for statins and β blockers, which were respectively more (adjusted odds ratio 1.48, 95% CI 1.10 to 1.98) and less (adjusted odds ratio 0.78, 95% CI 0.60 to 1.00) commonly prescribed to women. Conclusion : Results suggest that the poorer outcome for women after MI reported in other studies may reflect sex bias in management as well as differences in age and co-morbidity and support the view that if women have access to the same quality of care as men then survival will be the same.